Mapping the Influence of the COVID-19 Pandemic on the Indian Economy : Insights from the Smart PLS-SEM Approach with IPMA - Singh, Raj Kumar; Kumar, Ajay; Singh, Yashvardhan (Indian Journal of Finance, 2024)
This research paper aimed to empirically evaluate the impact of the COVID-19 pandemic on the economies of India and Himachal Pradesh. The purpose of the study was to measure the pandemic’s economic severity and learn lessons for formulating policies to manage future crises. Utilizing secondary data, the study employed a descriptive research technique based on macroeconomic indicators to assess the pandemic’s effect on the Indian economy. A multivariate research technique based on the Smart PLS-SEM version 4.0 approach with IPMA was used to determine the effect of COVID-19 on the economy of Himachal Pradesh. Primary data were collected from 400 respondents using random sampling techniques for the analysis. The findings demonstrated that, with the exception of agriculture and related fields, the pandemic had a negative effect on every sector of the Indian economy. Additionally, the results revealed that various horticultural activities, such as production, finance, marketing, and human resources, had a positive and significant impact on the horticulture business, which in turn positively and significantly influenced the economy of Himachal Pradesh. Mediation research validated the importance of government initiatives in strengthening the connection between the horticulture business and the state’s economy. The IPMA analysis confirmed that the horticulture sector, in combination with government policies, had the potential to boost Himachal Pradesh’s economy. By presenting a conceptual model, this study contributed to the existing literature, enabling replication to analyze the effects of other disasters or crises. Moreover, it is one of the few studies that explicitly examined the relationship between business and the economy in the context of the pandemic.